PENGARUH PENGETAHUAN DAN LOKASI TERHADAP MINAT MENABUNG PADA BANK MUAMALAT INDONESIA CABANG PAREPARE PADA MASYARAKAT KELURAHAN LABUKKANG - Ruslan, Nurfitrah; Rahma, Rika (Program Studi Manajemen Fakultas Ekonomi dan Bisnis, 2022)
This study aims to determine whether there is an effect of knowledge and location on the interest in saving partially and simultaneously at Bank Muamalat Indonesia Cabang Parepare. This research was conducted in Labukkang Village, Parepare City using quantitative descriptive analysis. The method used is a quantitative method with data collection techniques used are questionnaires, observations and literature studies, questionnaires are distributed to the people of Labukkang Village, while the number of samples is 100 people, the data analysis techniques used are descriptive analysis, multiple linear regression analysis, validation test and reliability, regression analysis assumption method and hypothesis testing. Public knowledge and strategic locations can increase public interest in saving at Bank Muamalat. Based on the test results, it is known that knowledge has a positive and significant effect on the interest in saving. Based on the test results, it is known that the location has a positive and significant effect on the interest in saving. The results of this study indicate that knowledge and location partially and simultaneously has effect the interest in saving.